Peningkatan Pemahaman Perkalian dan Pembagian Siswa Kelas III melalui Permainan Math Market di Aik Berik - Zuria Mustika Rini; Helmi Helmi; Djuita Hidayati (FONDATIA, 2026)
Low conceptual understanding of multiplication and division in mathematics is one of the problems found among third-grade students at SDN Aik Berik, particularly in understanding multiplication as repeated addition and division as the process of dividing into equal groups. This condition is reinforced by a learning process that is still dominated by the lecture method, resulting in less active students and less meaningful learning. This study aims to determine the improvement in students’ conceptual understanding of multiplication and division through the implementation of the Math Market game among third-grade students at SDN Aik Berik, North Batukliang. This study used Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 39 third-grade students. Data were collected through tests, observation, and documentation using instruments in the form of teacher activity observation sheets, student activity observation sheets, and learning achievement tests. The data were analyzed quantitatively to determine individual and classical mastery, and qualitatively to determine student activity and the implementation of the Math Market game. The results show that the implementation of the Math Market game can improve students’ conceptual understanding of multiplication and division. In Cycle I, the students’ average score reached 67.17 with classical mastery of 56.41%, then increased in Cycle II to 87.17 with classical mastery of 90%. Teacher activity increased from 72.22% to 80%, while student activity increased from 57.33% to 77.33%. These findings indicate that the Math Market game is effective for improving students’ conceptual understanding of multiplication and division. This study contributes to the development of contextual educational game-based mathematics learning strategies and provides practical implications for elementary school teachers in creating mathematics learning that is more active, engaging, and meaningful.